Hibah Harta Orang Sakit Perspektif Maqashid Syariah (Analisis Pendapat Wahbah Al-Zuhaili Dan KHES) - Nugroho, Luthfiah Huzaimah; Nasution, Abdul Halim; Hafifah, Mutia (Jurnal Landraad, 2024)
A gift is a voluntary gift agreement without compensation, either to heirs or other people. However, its implementation will have an impact on conflict when the grantor suffers from illness. Of course, this has different legal implications than for healthy people. This study focuses on the opinions of Wahbah Al-Zuhaili and KHES. This research method uses library research which is qualitative analytical in nature through a historical approach and a statute approach. By examining the history of KHES figures and texts. The data analysis method is using the fiqh muqaran approach. The results of the research show that first, the law of giving sick people with maqasid sharia values is found in the aspects: Protecting religion, protecting the soul, protecting the mind, protecting property, protecting offspring. Second, Wahbah al-Zuhaili classified illness conditions, namely: serious illness and non-severe illness. Conditions of serious illness that cause death before oneyearhas passed, the law applies to grant people who are seriously ill cause death. Meanwhile, for illnesses that are not serious or that do not cause death, the grantor may make a commitment with the recipient of the grant to pay for life until death, as stated in article 454 paragraph 2. Third, KHES specifically includes grants for seriously ill people in article 724 -727.